Exploring Gender Bias in the Dual Continua of Mental Health Measurement: Differential Item Functioning Analysis - Aziz, Rahmat; Mangestuti, Retno; Alribdi, Nada Ibrahim; Ali, Maqdisi Firdaus (FAKULTAS PSIKOLOGI UIN SYARIF HIDAYATULLAH JAKARTA, 2026)
Gender differences in mental health are widely reported, yet few studies have examined whether commonly used assessment instruments function equivalently across gender at the item level, particularly within the Dual Continua Model of Mental Health. The present study addresses this gap by evaluating gender-related measurement bias using regression-based Differential Item Functioning (DIF) analysis. A total of 1,674 university students from 32 Indonesian institutions completed the Azira Mental Health Scale (AMHS-24), which measures psychological well-being and psychological distress. DIF was assessed by controlling for latent trait levels to determine whether males and females respond differently to items at equivalent levels of psychological functioning. Results indicate that most well-being items exhibited no DIF, suggesting structural stability across gender for positive emotion, social relationship, and life satisfaction domains. In contrast, several distress items demonstrated uniform and nonuniform DIF, with one item showing strong magnitude. These findings suggest that the distress dimension may be more sensitive to gender-related response tendencies than the well-being dimension. By integrating the dual-continua framework with item-level psychometric analysis, this study clarifies whether observed gender differences reflect construct-relevant variance or differential item functioning, thereby contributing to the theoretical refinement and measurement fairness of mental health assessment.